High-uniformity high-frequency copper-clad plate, preparation method thereof and printed circuit board

Through the method of impregnation of silane coupling agent solution and superposition of PTFE film, the environmental hazards and uniformity problems in the preparation of existing PTFE-based copper clad plates are solved, and the preparation of high uniformity and high-frequency copper clad plates is achieved, which improves dielectric performance and production environmental protection.

CN119697885APending Publication Date: 2025-03-25SHENZHEN NAFLUOR TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411866019.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing preparation methods for PTFE-based copper clad plates have environmental hazards, poor uniformity of PTFE content, unevenness of dielectric constant and loss angle, and chromatic aberration.

Method used

After impregnating the glass fiber cloth with a silane coupling agent solution, it is superimposed with the PTFE film to form a PTFE film dielectric layer, then superimposed with copper foil, and hot-pressing to prepare a high-uniform high-frequency copper clad plate.

Benefits of technology

The production process without environmental pollution is achieved, the uniformity of PTFE content and dielectric properties of copper clad plate are improved, the production cost is reduced, and the occurrence of color difference is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119697885A_ABST
    Figure CN119697885A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of communication electronic materials, and discloses a high-uniformity high-frequency copper-clad plate, a preparation method thereof and a printed circuit board, and the method comprises the following steps: (1) impregnating glass fiber cloth with a silane coupling agent solution to obtain alkylated glass fiber cloth, and laminating the alkylated glass fiber cloth with a PTFE film to obtain a PTFE laminated film; a PTFE film dielectric layer is obtained; (2) laminating the PTFE film dielectric layer and a copper foil, putting the laminated composite layer between two mirror steel plates, combining to obtain a raw material, and then carrying out hot press molding on the combined raw material; wherein in the silane coupling agent solution, a silane coupling agent is 3-amino propyl trimethoxy silane and / or 3-amino propyl triethoxy silane, and the silane coupling agent is a silane coupling agent; and in the composite layer, the copper foil is in contact with the PTFE film in the PTFE film dielectric layer. According to the method provided by the invention, the high-frequency copper-clad plate with extremely high uniformity, stable dielectric constant Dk and extremely low dielectric loss Df can be prepared, and the production process is environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of communication electronic materials, and in particular to a high-uniformity high-frequency copper-clad laminate and a preparation method thereof, and a printed circuit board. Background Art

[0002] Due to the high purity and good uniformity of polytetrafluoroethylene (PTFE), stable dielectric constant, extremely low loss and strong adhesion to copper foil, PTFE-based copper clad laminates have excellent dielectric conductivity properties, and the electrical industry, such as radar, satellite communications, power amplifiers, low noise amplifiers, satellite tuners, low loss antennas, broadcast transmitters and other microwave circuits, has an increasing demand for them. Glass fiber cloth reinforced PTFE copper clad laminate type is the most commonly used high-frequency copper clad laminate due to its high strength, light weight, durability and high molding ability.

[0003] At present, most PTFE-based copper-clad laminates are obtained by impregnating glass fiber cloth with PTFE emulsion and repeatedly gluing to obtain different dielectric constants (D k ), material loss angle (D f ) and other characteristic requirements. Generally, the PTFE emulsion gluing of glass fiber cloth needs to be repeated more than 4 times (one PTFE emulsion dipping plus one baking is one gluing process), so as to control the proportion of PTFE to 65% to 97% (the rest is glass fiber).

[0004] Since the PTFE emulsion used in copper clad laminates generally contains about 60% solid content of PTFE micropowder, water accounts for about 30-35% of the weight, and additives such as ammonium perfluorooctanoate account for about 5-10% of the weight, during the baking process after the glass fiber cloth is impregnated with PTFE emulsion, ammonium perfluorooctanoate will volatilize and decompose at high temperatures, posing obvious environmental hazards.

[0005] In addition, the viscosity of PTFE emulsion is low (0.015-0.1020Pa·s), and the sag phenomenon is serious when it is combined with glass fiber cloth during the impregnation process, thus forming obvious flow marks on the surface of the film. When the plate is formed at high temperature, it is difficult to squeeze and flatten the flow marks formed on the surface of the film because the non-melt viscosity of PTFE is very high, that is, the fluidity is very poor. The local PTFE content uniformity of the obtained copper clad laminate is poor, which affects the material D k , D f uniformity, and sometimes even produce serious color differences. Summary of the invention

[0006] The purpose of the present invention is to overcome the obvious environmental hazards existing in the existing copper clad laminate preparation method, the poor uniformity of the local PTFE content of the obtained copper clad laminate, and the poor uniformity of the obtained material D k , D fIn order to solve the problem of non-uniformity and serious color difference, a high-frequency copper clad laminate with high uniformity and a preparation method thereof and a printed circuit board are provided.

[0007] In order to achieve the above object, the present invention provides a method for preparing a high-uniformity high-frequency copper-clad laminate, the method comprising the following steps:

[0008] (1) impregnating a glass fiber cloth with a silane coupling agent solution to obtain an alkylated glass fiber cloth, and laminating the alkylated glass fiber cloth with a PTFE film to obtain a PTFE film dielectric layer;

[0009] (2) laminating the PTFE film dielectric layer and the copper foil, placing the laminated composite layer between two mirror steel plates to obtain a raw material, and then hot pressing the raw material;

[0010] Wherein, in the silane coupling agent solution, the silane coupling agent is 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane;

[0011] In the composite layer, the copper foil is arranged in contact with the PTFE film in the PTFE film dielectric layer.

[0012] Preferably, in step (1), the ratio of the glass fiber cloth to the silane coupling agent solution is 1 g: 0.1-1 mL.

[0013] Preferably, in step (1), the concentration of the silane coupling agent solution is 50 to 98 wt %.

[0014] Preferably, in step (1), the PTFE film dielectric layer comprises a PTFE film, an alkylated glass fiber cloth and a PTFE film arranged in sequence.

[0015] Preferably, in step (2), the number of the copper foils in the composite layer is 1 or 2.

[0016] Preferably, in step (2), the composite layer comprises copper foil, PTFE film, alkylated glass fiber cloth, PTFE film, and copper foil arranged in order from top to bottom; or,

[0017] In step (2), the composite layer includes copper foil, PTFE film, alkylated glass fiber cloth, and PTFE film arranged in sequence from top to bottom.

[0018] Preferably, in step (2), the temperature of the hot pressing molding is 200-400°C, preferably 370-395°C.

[0019] Preferably, in step (2), the pressure of the hot pressing molding is 2 to 65 kg / cm 2 .

[0020] Preferably, in step (2), the hot pressing molding conditions also include: a time of 30 to 480 min and a vacuum degree of 5 to 80 mmHg.

[0021] A second aspect of the present invention provides a high-frequency copper-clad laminate, which is prepared by the method described above.

[0022] A third aspect of the present invention provides a printed circuit board, wherein the printed circuit board comprises the high-frequency copper clad laminate as described above.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. In the method provided by the present invention, it is not necessary to use PTFE emulsion to impregnate the glass fiber cloth. k The amount of ammonium perfluorooctanoate in the manufacturing process of the target product is zero, and no toxic fluoride, nitrogen oxides and ammonia smoke are produced in the production process, and no smoke is emitted, achieving the green and environmentally friendly production process;

[0025] 2. In the method provided by the present invention, k The PTFE required by the target product is added in the form of PTFE film to meet the PTFE content requirement. The glass fiber cloth is pretreated with a silane coupling agent. The resulting copper clad laminate has a higher uniformity. The thickness uniformity of the produced copper clad laminate is within 2%. k The value has been improved from the industry average of ±2-3% to within ±0.5%.

[0026] 3. In the method provided by the present invention, no PTFE gluing machine or high-temperature impregnation equipment investment is required, which shortens the process flow, reduces the links that cause product defects, reduces production costs, and improves the consistency and stability of the resulting PTFE-based copper-clad laminate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the stacking of double-sided copper clad laminate raw materials and the finished copper clad laminate structure;

[0028] Figure 2 It is a schematic diagram of the structure of the single-sided copper clad laminate raw materials and the finished copper clad laminate. DETAILED DESCRIPTION

[0029] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] The existing glass fiber cloth reinforced PTFE-based high-frequency copper-clad laminate manufacturing process is basically limited to: (1) obvious environmental hazards; (2) the local PTFE content uniformity of the obtained copper-clad laminate is poor, thus affecting the material D k , D f uniformity, and sometimes even produce serious color differences.

[0032] In view of this, the present invention provides a method for preparing a high-frequency copper clad laminate. In some embodiments, the method comprises the following steps:

[0033] (1) impregnating a glass fiber cloth with a silane coupling agent solution to obtain an alkylated glass fiber cloth, and laminating the alkylated glass fiber cloth with a PTFE film to obtain a PTFE film dielectric layer;

[0034] (2) laminating the PTFE film dielectric layer and the copper foil, placing the laminated composite layer between two mirror steel plates to obtain a raw material, and then hot pressing the raw material;

[0035] Wherein, in the silane coupling agent solution, the silane coupling agent is 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane;

[0036] In the composite layer, the copper foil is arranged in contact with the PTFE film in the PTFE film dielectric layer.

[0037] In the present invention, a PTFE film having good uniformity and not containing glass fiber cloth impregnated with PTFE emulsion is provided, and a method for preparing a PTFE film copper-clad laminate is provided without using a PTFE emulsion gluing and impregnating glass fiber cloth, thereby not only reducing environmental pollution and toxic emissions, but also improving the structure or thickness uniformity and D k , D f uniformity.

[0038] In some embodiments, in step (1), the silane coupling agent solution comprises a silane coupling agent (3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane) and ethanol.

[0039] The present invention does not limit the amount relationship between the glass fiber cloth and the silane coupling agent solution during the impregnation in the step (1), as long as the silane coupling agent solution can immerse the glass fiber cloth. Considering the impregnation effect and cost, in a preferred embodiment, in the step (1), the amount ratio of the glass fiber cloth to the silane coupling agent solution is 1g: 0.1-1mL. Specifically, the amount ratio of the glass fiber cloth to the silane coupling agent solution can be, for example, 1g: 0.1mL, 1g: 0.2mL, 1g: 0.3mL, 1g: 0.4mL, 1g: 0.5mL, 1g: 0.6mL, 1g: 0.75mL, 1g: 0.8mL or 1g: 1mL.

[0040] In a preferred embodiment, in step (1), the concentration of the silane coupling agent solution is 50-98wt%. Under the above solid-liquid ratio and silane coupling agent solution concentration, the high-frequency copper clad laminate finally obtained has better uniformity and better overall performance.

[0041] Further preferably, in step (1), the concentration of the silane coupling agent solution is 60 to 95 wt %.

[0042] In a preferred embodiment, the silane coupling agent solution is a solution prepared from a silane coupling agent (3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane) and ethanol, wherein the concentration of the silane coupling agent is 60 to 95 wt %.

[0043] In the present invention, the specific lamination method of the alkylated glass fiber cloth and the PTFE film in step (1) is not particularly limited, and can be combined according to the requirements of different dielectric constants and thicknesses. In some embodiments, the PTFE film dielectric layer includes a stacked PTFE film and an alkylated glass fiber cloth.

[0044] In other embodiments, the PTFE film medium layer includes a PTFE film, an alkylated glass fiber cloth and a PTFE film arranged in sequence.

[0045] In other embodiments, the PTFE film dielectric layer includes a PTFE film, an alkylated glass fiber cloth, a PTFE film, an alkylated glass fiber cloth, and a PTFE film arranged in sequence.

[0046] In a preferred embodiment, the PTFE film dielectric layer includes a PTFE film (upper layer), an alkylated glass fiber cloth (middle layer) and a PTFE film (lower layer) arranged in sequence from top to bottom. By selecting the PTFE film dielectric layer of the above structure, the combined operation is simple and the high-frequency copper clad laminate finally obtained has good performance.

[0047] The present invention does not impose any particular limitation on the specific source of the PTFE film in step (1), which may be purchased or prepared according to conventional methods in the art.

[0048] In the method of the present invention, in step (2), the number of the copper foils in the composite layer can be 1 or 2. When there is 1 copper foil in the composite layer, the copper foil and the PTFE film dielectric layer are stacked to finally produce a single-sided copper-clad laminate; when there are 2 copper foils in the composite layer, the PTFE film dielectric layer is arranged between the two copper foils to finally produce a double-sided copper-clad laminate.

[0049] Please refer to Figure 1 In a specific embodiment, the composite layer includes copper foil, PTFE film, alkylated glass fiber cloth, PTFE film, and copper foil arranged in sequence from top to bottom. That is, in this embodiment, the number of copper foils is 2, and the PTFE film dielectric layer includes PTFE film, alkylated glass fiber cloth, and PTFE film arranged in sequence. Please refer to Figure 2 In another specific embodiment of the present invention, the composite layer includes copper foil, PTFE film, alkylated glass fiber cloth, and PTFE film arranged in sequence from top to bottom. That is, in this embodiment, the number of copper foils is 1, and the PTFE film dielectric layer includes PTFE film, alkylated glass fiber cloth, and PTFE film arranged in sequence.

[0050] In a preferred embodiment, in step (2), the temperature of the hot pressing molding is 200-400°C. At the above hot pressing molding temperature, the uniformity and stability of the obtained high-frequency copper clad laminate are better. Further preferably, the temperature of the hot pressing molding is 370-395°C, specifically, for example, 370°C, 375°C, 378°C, 380°C, 385°C, 390°C or 395°C, and most preferably 385°C.

[0051] In a specific embodiment, in step (2), the hot pressing is carried out in a vacuum high temperature press.

[0052] In a preferred embodiment, in step (2), the pressure of the hot pressing molding is 2 to 65 kg / cm 2 , more preferably 20 to 50 kg / cm 2 , specifically, for example, 20 kg / cm 2 , 25kg / cm 2 、30kg / cm 2 、33kg / cm 2 , 40kg / cm 2 , 45kg / cm 2 、48kg / cm 2or 50kg / cm 2 .

[0053] In a preferred embodiment, in step (2), the hot pressing molding time is 30 to 480 min, more preferably 180 to 300 min, specifically, for example, 180 min, 200 min, 220 min, 230 min, 240 min, 250 min, 260 min, 270 min, 280 min or 300 min.

[0054] In a preferred embodiment, in step (2), the vacuum degree of the hot pressing molding is 5 to 80 mmHg, preferably 5 to 15 mmHg.

[0055] The present invention also provides a high-frequency copper-clad laminate, wherein the high-frequency copper-clad laminate is prepared by the method described above.

[0056] The present invention also provides a printed circuit board, which comprises the high-frequency copper clad laminate as described above. Since the high-frequency copper clad laminate has good uniformity and high environmental protection, the printed circuit board comprising the high-frequency copper clad laminate has good comprehensive performance.

[0057] The present invention will be described in detail below by way of examples, but the protection scope of the present invention is not limited thereto. The experimental methods in the following examples, unless otherwise specified, are conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.

[0058] In the following examples and comparative examples, the raw materials used include:

[0059] Fiberglass cloth size: 19 inches x 25 inches;

[0060] Copper foil size: 19 inches x 25 inches;

[0061] PTFE film dimensions: 19" x 25".

[0062] Example 1

[0063] (1) using 3-aminopropyltrimethoxysilane and ethanol to prepare a silane coupling agent solution with a concentration of 90 wt %; impregnating a glass fiber cloth with the silane coupling agent solution, wherein 0.5 mL of the silane coupling agent solution is added per 1 g of the glass fiber cloth to obtain an alkylated glass fiber cloth, and then sandwiching a PTFE film, an alkylated glass fiber cloth, and a PTFE film in order from bottom to top to obtain a PTFE film dielectric layer;

[0064] (2) The PTFE film dielectric layer obtained in step (1) and the copper foil are laminated in the order of copper foil, PTFE film dielectric layer, and copper foil from bottom to top to obtain a composite layer ( Figure 1 ), placing the composite layer between two mirror steel plates to obtain a raw material;

[0065] (3) pushing the raw material obtained by combining step (2) into a vacuum high temperature press for hot pressing to obtain a high-frequency PTFE-based copper clad laminate; wherein the conditions for hot pressing include: a temperature of 385° C., a pressure of 33 kg / cm 2 , time is 240min, vacuum degree is 5-15mmHg.

[0066] Example 2

[0067] (1) using 3-aminopropyltrimethoxysilane and ethanol to prepare a silane coupling agent solution with a concentration of 60 wt %; impregnating a glass fiber cloth with the silane coupling agent solution, wherein 0.75 mL of the silane coupling agent solution is added per 1 g of the glass fiber cloth to obtain an alkylated glass fiber cloth, and then sandwiching a PTFE film, an alkylated glass fiber cloth, and a PTFE film in order from bottom to top to obtain a PTFE film dielectric layer;

[0068] (2) The PTFE film dielectric layer and the copper foil obtained by combining in step (1) are stacked in the order of copper foil, PTFE film dielectric layer, and copper foil from bottom to top to obtain a composite layer ( Figure 1 ), placing the composite layer between two mirror steel plates to obtain a raw material;

[0069] (3) pushing the raw material obtained by combining step (2) into a vacuum high temperature press for hot pressing to obtain a high-frequency PTFE-based copper clad laminate; wherein the conditions for hot pressing include: a temperature of 385° C., a pressure of 33 kg / cm 2 , time is 240min, vacuum degree is 5-15mmHg.

[0070] Example 3

[0071] The method described in Example 1 was followed, except that 3-aminopropyltrimethoxysilane was replaced by 3-aminopropyltriethoxysilane.

[0072] Example 4

[0073] The method described in Example 2 was followed, except that 3-aminopropyltrimethoxysilane was replaced by 3-aminopropyltriethoxysilane.

[0074] Comparative Example 1

[0075] The method described in Example 1 is used for implementation, except that in step (1), the glass fiber cloth is not impregnated with a silane coupling agent solution.

[0076] Test Case

[0077] The high-frequency copper-clad laminates prepared in Examples 1-4 and Comparative Example 1 were tested, wherein the thickness was tested by laser multi-point thickness test; the dielectric properties were tested by the following test method: the dielectric constant and dielectric loss of the above samples were tested under 10 GHz frequency electron wave radiation conditions according to IPC-TM-6502.5.5.5C (1998) standard; the copper foil peel strength was tested according to IPC-TM-2.4.8 method. The test results are shown in Table 1 below.

[0078] Table 1

[0079]

[0080] It can be seen from the results in Table 1 that the dielectric constant D of the high-uniformity high-frequency copper-clad laminate prepared by the method provided by the present invention is k Stable, dielectric loss D f At the same time, Example 2 has a significantly more stable dielectric constant D k , extremely low dielectric loss D f and more uniform copper clad laminate thickness.

[0081] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the superposition of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a high-uniformity high-frequency copper-clad laminate, characterized in that: The method comprises the following steps: (1) impregnating a glass fiber cloth with a silane coupling agent solution to obtain an alkylated glass fiber cloth, and laminating the alkylated glass fiber cloth with a PTFE film to obtain a PTFE film dielectric layer; (2) laminating the PTFE film dielectric layer and the copper foil, placing the laminated composite layer between two mirror steel plates to obtain a raw material, and then hot pressing the raw material; Wherein, in the silane coupling agent solution, the silane coupling agent is 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane; In the composite layer, the copper foil is arranged in contact with the PTFE film in the PTFE film dielectric layer.

2. The method according to claim 1, characterized in that In step (1), the ratio of the glass fiber cloth to the silane coupling agent solution is 1 g: 0.1-1 mL; In step (1), the concentration of the silane coupling agent solution is 50 to 98 wt %.

3. The method according to claim 1, characterized in that In step (1), the PTFE film dielectric layer includes a PTFE film, an alkylated glass fiber cloth and a PTFE film which are arranged in sequence.

4. The method according to any one of claims 1 to 3, characterized in that: In step (2), the number of the copper foils in the composite layer is 1 or 2.

5. The method according to any one of claims 1 to 4, characterized in that: In step (2), the composite layer includes copper foil, PTFE film, alkylated glass fiber cloth, PTFE film, and copper foil arranged in order from top to bottom; or, In step (2), the composite layer includes copper foil, PTFE film, alkylated glass fiber cloth, and PTFE film arranged in sequence from top to bottom.

6. The method according to any one of claims 1 to 5, characterized in that: In step (2), the temperature of the hot pressing molding is 200-400°C, preferably 370-395°C.

7. The method according to any one of claims 1 to 6, characterized in that: In step (2), the pressure of the hot pressing molding is 2 to 65 kg / cm 2 .

8. The method according to any one of claims 1 to 7, characterized in that: In step (2), the hot pressing molding conditions also include: time of 30 to 480 minutes and vacuum degree of 5 to 80 mmHg.

9. A high frequency copper clad laminate, characterized in that: The high-frequency copper-clad laminate is prepared by the method described in any one of claims 1 to 8.

10. A printed circuit board, characterized in that: The printed circuit board comprises the high-frequency copper clad laminate according to claim 9.